2011
DOI: 10.1111/j.1399-6576.2011.02434.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl starches and dextran during hip replacement surgery: effects on blood volume and coagulation

Abstract: All tested colloid fluids induced a mild hypercoagulable state with faster clotting, but with weaker clot strength. The additive influence of surgery was relatively small, and postoperative changes in coagulation were mainly due to differences in the half-life of each colloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…17 We previously reported that both aPTT and PT-INR increased by 5-10% with the infusion of various colloid fluids during hip replacement surgery, but the timing was such that the strengthening of the coagulation could only be captured by the clotting time as measured by ROTEM. 16 Infusion of 10 ml/kg of albumin 5% also increased aPTT and PT-INR by about 5%. A rebound reduction in aPTT developed during the first 30 min after the infusion ended, but it never went below baseline.…”
Section: Marker Of Dilutionmentioning
confidence: 96%
See 1 more Smart Citation
“…17 We previously reported that both aPTT and PT-INR increased by 5-10% with the infusion of various colloid fluids during hip replacement surgery, but the timing was such that the strengthening of the coagulation could only be captured by the clotting time as measured by ROTEM. 16 Infusion of 10 ml/kg of albumin 5% also increased aPTT and PT-INR by about 5%. A rebound reduction in aPTT developed during the first 30 min after the infusion ended, but it never went below baseline.…”
Section: Marker Of Dilutionmentioning
confidence: 96%
“…Moreover, our previous publications show that both hydroxyethyl starch and 5% albumin expand the plasma volume by 80-100% rather than by 40%. 2,9,16 The activated partial thromboplastin time (aPTT) and prothrombin international normalised ratio (PT-INR) are screening analyses that disclose shifts in the intrinsic and extrinsic blood coagulation pathways respectively. Coagulation factors of the intrinsic pathway are generally larger than the extrinsic pathway proteins.…”
Section: Marker Of Dilutionmentioning
confidence: 99%
“…It has been shown to have good PV expanding properties, in some studies even superior to that of all other colloids studied, in states of normal capillary permeability 18,19 and in states of increased capillary permeability. 20,21 Based on recent studies, the use of HES is no longer recommended in sepsis, 22 which has reduced the synthetic colloid treatment alternatives in the critically ill patients to a minimum.…”
mentioning
confidence: 96%
“…Zdolsek et al compared different types of HES with 6% dextran 70 (Zdolsek et al 2011). They found better perioperative haemodynamics with dextran, but no major coagulation, bleeding, or transfusion differences between the colloids.…”
Section: Discussionmentioning
confidence: 99%
“…There are only two recent randomised clinical studies on haemostasis and bleeding complications after perioperative dextran use (Rasmussen et al 2015; Zdolsek et al 2011). …”
Section: Introductionmentioning
confidence: 99%